Functional dental occlusion: an anthropological perspective and implications for practice. (21st January 2014) - Kaidonis, JA; Ranjitkar, S; Lekkas, D; Brook, AH; Townsend, GC
Abstract: Physiologic changes occur in dental occlusion throughout life, resulting from the interplay between functional demands and reciprocating adaptive responses. These changes have been reported in the anthropological literature and they reflect evolutionary changes in the human stomatognathic system during the Paleolithic, hunter‐gatherer period. Specific occlusal changes occur in response to different environments, leading to extensive variation within and between extinct and extant human populations. For example, functional demands can cause occlusal and interproximal tooth wear, resulting in shortening of the dental arch, continual tooth eruption and changes in masticatory patterns. Since the advent of farming through to our current industrialized culture, functional demands on the human masticatory system, and its adaptive responses to these demands, have been reduced considerably. Indeed, it is only occasionally that functional demands are severe enough to lead to obvious pathology in the modern human dentition. In contrast to normal masticatory activity, 'modern‐day conditions' such as dental caries, periodontal disease and erosion, can lead to significant changes in dental occlusion that are pathological and need to be treated. The masticatory system is a dynamic, functional unit that displays considerable change over a lifetime. In this concept paper, it is proposed that modern human populations living in industrialized environments display dental occlusions that can be considered to be 'neotenous'; that is, our dentitions tend to reflect an unworn stage of our ancestors that was only seen in infants, juveniles and young adults. Clinicians can draw on both phylogenetic and ontogenetic perspectives of 'functional dental occlusion' to differentiate continual physiological changes occurring over time that require ongoing review, from pathological responses that require intervention.